The method to mitigate the impact of high penetration of solar photovoltaic capacity to the grid via analysis of the temporal variation of solar irradiance in Malaysia - Gan, Chun Liang (2019)
The begun of penetrate solar photovoltaic renewable energy, the first thing come to the mind was the intermittency factor. This project will provide the solution to mitigate the impact of high penetration of solar photovoltaic in Malaysia. The project will focus on the intermittency compensation and enhance the penetration level. The intermittency will be identified by using the station combination method including two quantify method, average the intermittency and perform standard deviation statistic. The analysis will perform on three main scenarios having the identical characteristic, the scenarios was categories as, good we ather condition, best compensation condition and most various condition. Followed by, the voltage drop method to justify the final output from the analysis was able to achieve the penetration level above 30%.